Mystical sound of Selonding from eastern Balinese ancient village - Nyoman Sabda (Bali Tourism Board, 2021)
Selonding is a part of Gamelan Tua, A rarely known musical instrument out of many Balinese gamelan. This sacred instrument can be found in several old villages in Karangasem regency, such as Bugbug, Prasi, Seraya, Tenganan Pegringsingan, Timbrah, Asak, Bungaya, Ngis, Bebandem, Besakih, Selat. However, some studies claimed that Gamelan Selonding today could only be seen in the Tenganan Pegringsingan and Bongaya villages. Selonding is the only type of iron-blade Balinese Gamelan. Low steel content on the iron ingot produces a softer sound texture than bronze gamelan, broadly used. The soft and rhythmic audio from Gamelan Selonding, according to the study, was said to reduce the elder’s anxiety level from moderate to mild. Despite its high cultural value and vital for the Bali Aga ritual, low exposure and promotion about Selonding Gamelan were reasons for the low interest and concern of young people in Bali for their own culture. To promote Selonding among Balinese, various studies proposed many mediums to attract public interest, including the documentary film production about the ancient instruments, and introduce an android-based application to learn playing Gamelan Selonding from users’ smartphones. Furthermore, today, Sekaa Selonding exists not only on Karangasem Regency but also in other parts of Bali since many Balinese youngsters outside Karangasem are interested in learning Gamelan Selonding.